Dairy deregulation and low-input dairy production: A bioeconomic evaluation - Tozer PR; Huffaker RG (Western Agricultural Economics Association, 1999)
Deregulation of the Australian dairy industry could affect the utilization of resources by milk producers and the profitability of dairy production. In this study we examine the feed mix that dairy producers use, both pastures and supplements, under partial and total deregulation. We are particularly interested in the interaction of pasture utilization and farm profitability. The results of this research demonstrate that profitable low-input dairying is constrained by the most limiting resource, feed supplied by pasture, and that the interactions between economic and biological processes are critical to farm profitability.
Keywords: Bioeconomics; Dairy production; Deregulation; Low-input dairying; Pasture utilization